RELEVANSI TRINITAS BAGI HIDUP MANUSIA MENURUT KARL RAHNER - Herman Punda Panda (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2020)
Karl Rahner made a major contribution to the trinitarian theology in this post-modern era. He has attempted to reconcile the classical doctrine of the Trinity with contemporary thought. Rahner spoke about the topic of the oneness and triadity of God. Regarding the oneness of God, Rahner did not speak about the one ousia / divine essence, but rather the unity or perichoresis of the three divine persons. What is called God here, is not the essence of divinity but the Father who is the source of the Son and the Holy Spirit. Furthermore, Rahner emphasizes the identification and relationship between the immanent Trinity and the economic Trinity which according to him is the important point in the theology of the Trinity. Consequently, the only starting point for developing a theology of the Trinity is the history of our experience with God, in which God reveals Himself in two ways, namely through the Word and the Spirit. This article presents Karl Rahner's thoughts on the Trinity and its relevance to human life. First of all, the author describes about the place of Trinitarian theology in the general framework of Rahner's anthropological theology. Next, it discussed his thoughts on the Trinity itself and at the end, the relevance of the Trinity to human life. This relevance becomes evident in Rahner's thought about the communication of God to man in the form of His Word and Spirit.